2002
DOI: 10.1097/00003246-200204000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of previous acute lung injury during neutropenia recovery*

Abstract: Patients with acute respiratory failure after prolonged neutropenia complicated by pneumonia are at increased risk for ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
4
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 35 publications
3
91
4
5
Order By: Relevance
“…Studies using various experimental models in animals have indicated that the severity of the ALI/ARDS course depends on the number of activated neutrophils infiltrating the lung (34). Although ARDS has been described in neutropenic patients (35), these findings do not exclude the central role of neutrophils in ARDS pathophysiology, because the recovery of patients from neutropenia was associated with deterioration of pulmonary function (36). Attenuation of neutrophil accumulation in the lungs, by using molecules inhibiting neutrophil adhesion, decreased the severity of lung injury (37).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using various experimental models in animals have indicated that the severity of the ALI/ARDS course depends on the number of activated neutrophils infiltrating the lung (34). Although ARDS has been described in neutropenic patients (35), these findings do not exclude the central role of neutrophils in ARDS pathophysiology, because the recovery of patients from neutropenia was associated with deterioration of pulmonary function (36). Attenuation of neutrophil accumulation in the lungs, by using molecules inhibiting neutrophil adhesion, decreased the severity of lung injury (37).…”
Section: Discussionmentioning
confidence: 99%
“…It is at this point that clinical and physiological manifestations of lung injury become first apparent. It is not surprising then, that the resolution of neutropenia is temporally associated with worsening lung function in neutropenic hosts [37]. Reports of ALI in neutropenic patients [38] merely emphasise the complexity and redundancy of disease mechanisms associated with lung injury.…”
Section: Biotraumamentioning
confidence: 99%
“…Neutrophils appear to play a major role in the development of ALI. Although ALI can occur in the setting of neutropenia, in both experimental models and in patients, neutrophils have been demonstrated to potentiate the pulmonary inflammatory response associated with ALI (4,5). Given the important role that neutrophils play in ALI, central questions in the pathophysiology of this entity relate to mechanisms that contribute to the accumulation and activation of neutrophils in the lung.…”
Section: A Cute Lung Injury (Ali)mentioning
confidence: 99%